In the manner of the Franks hunting, kingship, and masculinity in early medieval Europe - Goldberg, Eric J. 1969- (The Middle Ages Ser., 2020)
Featuring more than sixty illustrations, In the Manner of the Franks traces the long history of early medieval hunting from the fourth through the tenth centuries. Eric J. Goldberg focuses chiefly on elite men and the changing role that hunting played in articulating kingship, status, and manhood in the post-Roman world.